2015
DOI: 10.1038/mp.2015.97
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the rab5 effector APPL1 mediates APP-βCTF-induced dysfunction of endosomes in Down syndrome and Alzheimer’s disease

Abstract: β-amyloid precursor protein (APP) and its cleaved products are strongly implicated in Alzheimer’s Disease (AD). Endosomes are highly active APP processing sites and endosome anomalies associated with upregulated expression of early endosomal regulator, rab5, are the earliest known disease-specific neuronal response in AD. Here, we show that the rab5 effector APPL1 mediates rab5 over-activation in Down Syndrome (DS) and AD, which is caused by elevated levels of the β-cleaved carboxy-terminal fragment of APP (βC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
236
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(268 citation statements)
references
References 71 publications
16
236
0
Order By: Relevance
“…Endosomal abnormalities could result from accumulation of Aβ or CTF-β [32,64], Photographs illustrate APP exosomes localized on dendritic spine necks (empty arrowhead), dendritic spine heads (white arrowheads), or dendritic shaft (white arrow). Bar 10 μm.…”
Section: Discussionmentioning
confidence: 99%
“…Endosomal abnormalities could result from accumulation of Aβ or CTF-β [32,64], Photographs illustrate APP exosomes localized on dendritic spine necks (empty arrowhead), dendritic spine heads (white arrowheads), or dendritic shaft (white arrow). Bar 10 μm.…”
Section: Discussionmentioning
confidence: 99%
“…The activated oncogenes can induce angiogenesis with consequent infiltration and metastasis 32 and can inhibit apoptosis by inhibiting TP53 33 . Kim et al found that RAB5A (formerly RAB5) acting through appl1 mediation induced dysfunction of endosomes 34 . Recent studies showed that activation of RAB5A was a significant event in maintaining the dynamics of focal cellular adhesions, influencing not only cell migration, but also tumour cell invasion 35 .…”
Section: Discussionmentioning
confidence: 99%
“…C99 is able to bind directly to human adaptor protein, phosphotyrosine interaction, PH domain and leucine zipper containing 1, APPL1, which in turn recruits and pathologically activates Rab5, leading to cholinergic neurodegeneration in Down syndrome patient cells, i.e. cells carrying one extra copy of AβPP and thus expressing higher levels of the Aβ peptide (Kim et al, 2016). Furthermore, the amount of the C99 fragment has been shown to be higher in AD brains even though normal levels of AβPP were detected, and the same over-activation of Rab5 could also be observed in AD brains (Kim et al, 2016).…”
Section: Physiological Function Of Aβpp and Its Cleavage Productsmentioning
confidence: 99%
“…cells carrying one extra copy of AβPP and thus expressing higher levels of the Aβ peptide (Kim et al, 2016). Furthermore, the amount of the C99 fragment has been shown to be higher in AD brains even though normal levels of AβPP were detected, and the same over-activation of Rab5 could also be observed in AD brains (Kim et al, 2016). The C-terminal fragment produced after cleavage by α-secretase, C83, has no known function but it has been implicated as being involved in neurodegeneration (Rockenstein et al, 2005).…”
Section: Physiological Function Of Aβpp and Its Cleavage Productsmentioning
confidence: 99%
See 1 more Smart Citation